COFFEE AIR FRESHENER GEL PRODUCTION BASED ON KAPPA CARRAGEENAN, XANTHAN GUM, AGAR-AGAR WITH PATCHOULI OIL ADDITION - Rahma Aji Kurniawan; Siti Khodijah; Erwana Dewi; Taufik Jauhari (Politeknik Negeri Sriwijaya, 2022)
Air freshener products on the market generally use synthetic fragrances that are harmful to health. Air fresheners can be made from natural ingredients based on kappa carrageenan, xanthan gum, and agar, using coffee oil as a fragrance with and patchouli oil as a natural fixative can be aromatherapy to relieve stress and stimulate optimal brain performance. This research aims to obtain the best composition of kappa carrageenan, xanthan gum, agar and patchouli oil concentrations by comparing the research products with air freshener gel sample of commercial product. The method used is by varying the composition of kappa carrageenan, xanthan gum, and agar as a gelling agent;concentrations ofgelling agent 4 - 6% w / w; and concentration of patchouli oil 0 – 1.5%. Product analisys includes: gel strength, gel syneresis, gel viscosity at 80oC, moisture content, liquid evaporation and weight loss tests, GC-MS analysis, aroma retention test, and hedonic test. The fragrance gel product produced from a mixture of kappa carrageenan, xanthan gum, and agar with a ratio of 2: 1: 1 at concentration gelling agent 6% had the lowest syneresis 0.48% and gel strength 937.1891 gf / cm2. The addition of patchouli oil which was the most effective in maintaining fragrance, with the smallest total evaporation and weight loss was 1.5% and was quite favored by the panelists.